Parathyroid carcinoma and pheochromocytoma in a patient with neurofibromatosis type 1: a rare association - Jardelina Brena Rocha Leite; Nicole Ramalho De Freitas; Rafaella Nelice de Holanda Cardoso; Erik Trovão Diniz; Gabriel Rodrigues de Assis Ferreira; Fernão Henrique Costa e Alvim; Camila Ribeiro Coutinho Madruga; Ana Carolina Thé Garrido; Luciano Albuquerque; Patricia Sampaio Gadelha; Ruy Lyra; Lucio Vilar (Endocrinology, Diabetes & Metabolism Case Reports)
The case report outlines a 33-year-old woman with neurofibromatosis type 1 (NF1) presenting complex symptomatology including a cervical mass, bone pain and significantly elevated calcium and parathyroid hormone levels, indicative of parathyroid carcinoma accompanied by cystic fibrous osteitis. Intriguingly, an incidental finding of an adrenal nodule prompted investigation, leading to the diagnosis of pheochromocytoma. Surgical intervention confirmed the presence of pheochromocytoma and parathyroid carcinoma. Genetic analysis corroborated NF1 with a pathogenic variant in the NF1 gene. The patient’s clinical manifestations, coupled with the presence of café-au-lait spots and axillary freckles, supported the diagnosis of NF1. This case not only highlights the challenging diagnostic landscape of NF1 but also underscores the rarity of the co-occurrence of parathyroid carcinoma and pheochromocytoma within the context of NF1. It emphasizes the necessity for heightened clinical suspicion and comprehensive evaluation in patients with NF1, particularly in those presenting with endocrine abnormalities. Further investigation into the underlying mechanisms linking these conditions is warranted to elucidate their pathophysiological interplay and inform optimal therapeutic strategies for affected individuals. This case underscores the importance of multidisciplinary collaboration in the management of complex NF1-associated manifestations, with an emphasis on early detection and tailored intervention to optimize patient outcomes.